2020
DOI: 10.1111/vsu.13426
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic localization of the deepest portion of the femoral trochlear groove in healthy dogs

Abstract: Objective: To validate a computed tomographic (CT) method to measure the femoral trochlear groove depth (FTGD). Study design: Cadaveric study. Sample population: Fifteen dogs, 26 femoral trochleae. Methods: Five points were identified from proximal to distal (proximal point [PP], P25, P50, P75, and distal point [DP]) along the trochlea via three-dimensional volume-rendering function on the sagittal plane and measured on multiplanar reconstruction images. Each rater repeated measurements in duplicate, unaware o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Nicetto and colleagues measured the femoral trochlear depth in dogs without stifle disorders, and also found that the deepest point of the femoral trochlea was located in the proximal part of the femoral trochlea. 20 Considering that the articular congruence of the proximal aspect of the patellofemoral joint is thought to be crucial for patellar instability in both human and veterinary medicine, 21 22 measuring the femoral trochlear morphology on the standardized measuring location in the present study was appropriate for the evaluation of the femoral trochlear morphology in dogs.…”
Section: Discussionmentioning
confidence: 96%
“…Nicetto and colleagues measured the femoral trochlear depth in dogs without stifle disorders, and also found that the deepest point of the femoral trochlea was located in the proximal part of the femoral trochlea. 20 Considering that the articular congruence of the proximal aspect of the patellofemoral joint is thought to be crucial for patellar instability in both human and veterinary medicine, 21 22 measuring the femoral trochlear morphology on the standardized measuring location in the present study was appropriate for the evaluation of the femoral trochlear morphology in dogs.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, Petazzoni and colleagues proposed a method for trochlear groove depth measurement using CT in normal dogs. 12,13 In the present study, sequential analysis of the distal femur was conducted including both the trochlear groove and the femoral condyle using 3D-CT imaging in dogs with grade 2 and 4 MPL. As a result, the morphology of the distal femur can be assessed at various locations, regardless of the positioning.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, computed tomography (CT) has been increasingly used to evaluate bone abnormalities in dogs. [11][12][13] In 2016, Yasukawa and colleagues reported that Toy Poodles with grade 4 MPL had significant femoral varus deformity, medial displacement of the tibial tuberosity, internal rotation of the proximal tibia and hypoplasia of the patella as observed using three-dimensional (3D) CT. 14 However, the depth of the trochlear groove and the morphology of the femoral condyles were not evaluated objectively due to lack of appropriate landmarks.…”
Section: Introductionmentioning
confidence: 99%
“…In available scientific literature, only 2 studies reported the trochlear depth and shape in healthy dogs but in medium-size and large breeds [15,17] although medial patellar luxation is commonly seen in small dog breeds. That is why our attention was focused on 4 small breeds: Mini-Pinscher, Pomeranian, Chihuahua and Yorkshire terrier.…”
Section: Discussionmentioning
confidence: 99%